Tumor de Glomus Carotídeo, a propósito de dos casos diagnosticados y operados en el área de cirugía Hospital Clínica Moderna Ibarra: Carotid Glomus Tumor, about two cases diagnosed and operated in the area of surgery Hospital Clínica Moderna Ibarra (La U Investiga, 2018)
Tumors of the carotid body or paragangliomas are rare lesions. They can become bilateral. Most are sporadic, family members associated with various genetic syndromes. Compared with the sporadic appearance, family presentation tends to appear at younger ages and to have multiple localization. It is the presentation of 2cases diagnosed and operated at the modern Ciudad de Ibarra Clinic.
Keywords: Tumors of the carotid body; Paragangliomas